Enhancing Sustainability Education in Maritime Cadet Training - Siahaan, Rosna Yuherlina; Malau, April Gunawan; Herawati , Susi (Universitas Pahlawan Tuanku Tambusai, 2024)
This research explores the integration of sustainability concepts into maritime training programs for cadets, focusing on curriculum content, teaching methods, and challenges. Through qualitative analysis, the study identifies a strong emphasis on renewable energy and practical exercises, with opportunities for improvement in energy efficiency and industry engagement. Challenges such as resource constraints and resistance to change are highlighted, underscoring the need for collaborative efforts to promote sustainability within maritime education. The findings emphasize the importance of enhancing curriculum content and teaching methods to prepare cadets for the environmental challenges facing the maritime industry. By addressing these challenges and fostering a culture of sustainability, stakeholders can play a vital role in shaping the future of the maritime sector. The research contributes to a better understanding of sustainability education in maritime training and provides insights to inform future initiatives aimed at fostering environmental stewardship among future maritime professionals.